Adjunctive ultrasound-guided vagus nerve-targeted pharmacopuncture for refractory fibromyalgia with autonomic symptoms: a case report - Ju-Hyun Lee; Young-Ung Lee; Tan-Hyuk Choi; Suji Lee; Seunghoon Lee (Frontiers in Medicine, 2026)
Fibromyalgia (FM) is a clinical syndrome characterized by chronic widespread pain and various functional symptoms. Although multiple treatments have been proposed for FM, therapeutic options remain limited for patients who do not respond adequately to conventional treatments. This case report describes a woman in her late 50s with refractory FM who received ultrasound-guided vagus nerve-targeted pharmacopuncture (UGP) as an adjunct to multimodal Korean medicine treatment. The patient presented with widespread pain, xerostomia, dyspepsia, headache, palpitations, and insomnia. Multimodal treatment included manual acupuncture, electroacupuncture, routine pharmacopuncture, wet cupping, and herbal medicine, with two additional UGP sessions administered during the treatment period. During the treatment course, the patient’s pain intensity decreased from 7 to 2 on the numeric rating scale, accompanied by improvements in sleep, fatigue, anxiety, depression, and patient-reported autonomic symptoms. Heart rate variability parameters also changed between baseline and the 3-month follow-up. No serious or persistent procedure-related adverse events were observed. However, because UGP was administered as part of a multimodal treatment program and HRV was assessed at only two time points, the specific contribution of UGP to the clinical and physiological changes could not be determined. This case provides a hypothesis-generating observation that warrants further investigation of vagus nerve-targeted interventions in FM.